Interleukin 6–dependent genomic instability heralds accelerated carcinogenesis following liver regeneration on a background of chronic hepatitis. Issue 5 (23rd March 2017) - Lanton, Tali; Shriki, Anat; Nechemia‐Arbely, Yael; Abramovitch, Rinat; Levkovitch, Orr; Adar, Revital; Rosenberg, Nofar; Paldor, Mor; Goldenberg, Daniel; Sonnenblick, Amir; Peled, Amnon; Rose‐John, Stefan; et al.
Abstract : Liver cancer, which typically develops on a background of chronic liver inflammation, is now the second leading cause of cancer mortality worldwide. For patients with liver cancer, surgical resection is a principal treatment modality that offers a chance of prolonged survival. However, tumor recurrence after resection, the mechanisms of which remain obscure, markedly limits the long‐term survival of these patients. We have shown that partial hepatectomy in multidrug resistance 2 knockout (Mdr2 –/– ) mice, a model of chronic inflammation‐associated liver cancer, significantly accelerates hepatocarcinogenesis. Here, we explore the postsurgical mechanisms that drive accelerated hepatocarcinogenesis in Mdr2 –/– mice by perioperative pharmacological inhibition of interleukin‐6 (IL6), which is a crucial liver regeneration priming cytokine. We demonstrate that inhibition of IL6 signaling dramatically impedes tumorigenesis following partial hepatectomy without compromising survival or liver mass recovery. IL6 blockade significantly inhibited hepatocyte cell cycle progression while promoting a hypertrophic regenerative response, without increasing apoptosis. Mdr2 –/– mice contain hepatocytes with a notable persistent DNA damage response (γH2AX, 53BP1) due to chronic inflammation. We show that liver regeneration in this microenvironment leads to a striking increase in hepatocytes bearing micronuclei, a marker of genomic instability, which is suppressed by IL6 blockade. Conclusion : Our findings indicate that genomic instability derived during the IL6‐mediated liver regenerative response within a milieu of chronic inflammation links partial hepatectomy to accelerated hepatocarcinogenesis; this suggests a new therapeutic approach through the usage of an anti‐IL6 treatment to extend the tumor‐free survival of patients undergoing surgical resection. (Hepatology 2017;65:1600‐1611)